PENGARUH PENGGUNAAN ABU CANGKANG KELAPA SAWIT TERHADAP STABILITAS MARSHALL PADA CAMPURAN LAPIS ASPAL BETON AC-BC (ASPHALT CONCRETE - BINDER COURSE) - Hermon Frederik Tambunan; Feny Fitratuz Zahro; Catur Marina, Bernaditha (Nusantara Hasana Journal, 2025)
Utilization of palm oil waste can be used as a road pavement material. In this study, the waste used in the form of palm oil shell ash. Availability of palm shell ash which is quite a lot is expected to provide better performance as a filler for mixture of asphalt concrete binder course (AC-BC). This study was conducted to determine the effect of the use of oil palm shell ash on marshall stability in laston AC-BC. Determination of the value of the Optimum Asphalt Content of the mixture was carried out by varying the content of the oil palm shell ash filler, namely 0%, 20%, 30%, 40%, 50% and 60%. Furthermore, the durability test or immersion by varying the temperature 25℃ and 60℃ with immersion time 4 hours, 24 hours and 48 hours. The result of this study obtained KAO values based on filler variations, namely 0% shell ash 5,6%, 20% shell ash 5,7%, 30% shell ash 5,725%, 50% shell ash 6%, and 60% shell ash 6,1%. The optimum stability was obtained at 1297,57kg at 40% filler variation of oil palm shell ash. Furthermore, the results of the durability test of the asphalt mixture obtained that the Residual Stability Index value at 0% filler variation with an immersion temperature of 25℃ was 93,176%, then at an immersion temperature of 60℃ was 90,390%. While at 40% filler variation the value of the Residual Stability Index obtained with an immersion temperature of 60℃ is 93,965%. This overall shows that the use of oil palm shell ash in asphalt mixtures still meets the minimum requirements of Bina Marga 2018 which is 90%.